If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 8x + 65 Multiply f * x fx = 8x + 65 Reorder the terms: fx = 65 + 8x Solving fx = 65 + 8x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 65x-1 + 8 Simplifying f = 65x-1 + 8 Reorder the terms: f = 8 + 65x-1
| 2(2x+1)=6x+1 | | 7/5=28/x | | P^2=91 | | 144x^4+1=0 | | x+y+5z=-14 | | 5/-10 | | x+y+7z=-22 | | 3(2x+5)-4x=5x | | 7x+21=9x-3 | | 0.02(5m-1.5)=0.4 | | X^2+17x+106=0 | | -2x+3=6x-17 | | Y^2+13y=146 | | 3v+16=61 | | x/21=1.4/3 | | 9x-2=7x+14 | | 52=4u+16 | | 2-(-y-6)=-7(-6y-7)+5 | | 21/x=3/1.4 | | 20=8-5(2x-3)+4 | | (9r-5)-(-4r-9)= | | 3gh-2g=0 | | 2v-12=10 | | 6-x-3=4[x-2] | | 8+7x+22x-2=180 | | 3x+23-24x=21x | | (9r-5)-(-4-9)= | | 5(x-4)3x=4 | | r-11=-10 | | 2x-5=-7x+4 | | 3q^2-6q=2q^2-8q+15 | | 6x+15=4x-2 |